2015
DOI: 10.1016/j.laa.2015.02.030
|View full text |Cite
|
Sign up to set email alerts
|

On the chromatic number of regular graphs of matrix algebras

Abstract: Let R be a ring and Z(R) be the set of zero divisors of R. The regular graph of R, denoted by Γ(R) is the graph with vertex set R\Z(R) and {X, Y } is an edge if X +Y ∈ Z(R). We prove that the chromatic number of Γ(M n (F q )) is at least (q/4) n/2 , where M n (F q ) is the ring of n × n matrices over F q , q being an odd prime power. This proves that the chromatic number of Γ(M n (F alg p )) is infinite, answering a case of a question posed in BCC22.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…More precisely, we will show that as q → ∞, we have χ(G G,S (F q )) → ∞. In fact, similar to [26] we will establish a polynomial lower bound for χ(G G,S (F q )). Further, we will also show that the large chromatic number is not due to the existence of large cliques; in fact, as we will see, the clique number of G G,S (F q ) is uniformly bounded as q → ∞ (see Proposition 1.7).…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…More precisely, we will show that as q → ∞, we have χ(G G,S (F q )) → ∞. In fact, similar to [26] we will establish a polynomial lower bound for χ(G G,S (F q )). Further, we will also show that the large chromatic number is not due to the existence of large cliques; in fact, as we will see, the clique number of G G,S (F q ) is uniformly bounded as q → ∞ (see Proposition 1.7).…”
Section: Introductionsupporting
confidence: 52%
“…Using Lang-Weil bound and representation theory of finite simple groups of Lie type, we will establish lower bounds on the chromatic number of a large family of these graphs. As a corollary we obtain a lower bound for the chromatic number of certain Cayley graphs associated to the ring of n × n matrices over finite fields, establishing a result for the case of SLn parallel to a theorem of Tomon [26] for GLn. Moreover, using Weil's bound for Kloosterman sums we will also prove an analogous result for SL2 over certain finite rings.2010 Mathematics Subject Classification.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…We will refine their result giving almost sharp bound on the clique number. Tomon [11] showed that the chromatic number of this graph is at least (q/4) ⌊n/2⌋ .…”
Section: Introductionmentioning
confidence: 99%
“…As has been mentioned in [2] a greedy method would be to iteratively pick, in a graph , an uncolored vertex , and to color it with the smallest color which is not yet used by its neighbors . Such a coloring will obviously stay proper until the whole vertex set is colored, and it never uses more than ∆( ) + 1 different colors, where ∆( ) is the maximal degree of , as in the procedure no vertex will ever exclude more than ∆( ) colors (for more details see [3][4][5][6][7][8]). Consider is a graph.…”
Section: Introductionmentioning
confidence: 99%